The beneficial effect of surface carbon coating on stress corrosion cracking of Type 304 austenitic stainless steels in high temperature water. (1st January 2019) - Mukahiwa, K.; Bertali, G.; Burke, M.G.; Duff, J.; Scenini, F.
Abstract: A pronounced improvement in stress corrosion cracking initiation resistance resulting from the presence of a carbonaceous surface film was investigated for specimens strained dynamically in hydrogenated high temperature water. Microstructural characterisation of the post-test samples indicated that this improvement in SCC resistance was promoted by the formation of a more uniform and thick surface oxide layer that prevented localized oxidation. Graphical abstract: Effect of C coating on primary water stress corrosion cracking. Unlabelled Image